2003
DOI: 10.1093/jee/96.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bifenthrin Treatment Zones Against Red Imported Fire Ant

Abstract: Exclusion of ants, particularly red imported fire ant, Solenopsis invicta (Buren), from homes, nursing facilities, hospitals, and electrical housings is an important strategy in urban and rural pest control. We conducted a laboratory bioassay to determine the repellency of granular bifenthrin (Talstar: rate 2.087 kg of formulated product/92.88 m2 or 4.6 lb formulated product/1000 feet2 or 4.2 g active ingredient/92.88 m2) to S. invicta foragers. In the field, we compared the efficacy of three widths (0.3, 2.0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Bifenthrin is an effective pyrethroid insecticide that is widely used in both agricultural and urban environments (34)(35)(36). However, due to its high toxicity against aquatic organisms and its potential risk to human health, bifenthrin residue in the environment has drawn increasing public concern (37-39).…”
Section: Resultsmentioning
confidence: 99%
“…Bifenthrin is an effective pyrethroid insecticide that is widely used in both agricultural and urban environments (34)(35)(36). However, due to its high toxicity against aquatic organisms and its potential risk to human health, bifenthrin residue in the environment has drawn increasing public concern (37-39).…”
Section: Resultsmentioning
confidence: 99%
“…Neoh et al, found after exposed to chlorantraniliprole termitea were likely to cease feeding and undergo starvation, which made the pesticide low efficiency 35 . Because in the management of social insect, repellent or fast-acting toxicant may provide effective barriers 36 . Non-radiolable rubidium (Rb) have been used as a good trace in termites' trophallaxis process [37][38][39] , but had not yet been reported in S.invicta.…”
Section: Discussionmentioning
confidence: 99%